2018
DOI: 10.1111/pan.13336
|View full text |Cite
|
Sign up to set email alerts
|

Oesophageal atresia: Are “long gap” patients at greater anesthetic risk?

Abstract: Long gap oesophageal atresia infants have a similar incidence of perioperative complications to other infants with oesophageal atresia. Current surgical approaches to long gap repair, however, are associated with longer anesthetic exposures and require multiple procedures in infancy to achieve oesophageal continuity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
(65 reference statements)
1
7
0
Order By: Relevance
“…VACTERL and CHARGE association and chromosomal anomalies were found in similar proportions to previous work . Some patients were under the care of the palliative care team or had reorientation of their care after surgery because of comorbidity.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…VACTERL and CHARGE association and chromosomal anomalies were found in similar proportions to previous work . Some patients were under the care of the palliative care team or had reorientation of their care after surgery because of comorbidity.…”
Section: Discussionsupporting
confidence: 80%
“…Knottenbelt et al defined ventilatory difficulty as either specific comments from the record, severe gastric distension or a significant hypoxemia, and found that it was recorded in 6.9% at induction and 14.9% intraoperatively. Powell et al found difficult airway management occurred in 7.1%, difficult intubation in 3.3% and intraoperative ventilation difficulty in 11.8% . Andropolous et al defined ventilation difficulty as significant hypoxemia or hypercarbia, elevated peak inspiratory pressures, or severe gastric distension, and found that 21% had difficulty with ventilation …”
Section: Discussionmentioning
confidence: 99%
“…Any interrelationships between intraoperative events, type of surgical approach—thoracoscopic or open—and (developmental) outcomes have not yet been elucidated. Comorbidities, intraoperative events like duration of surgery, the occurrence of hypercapnia (and its effect on cerebral autoregulation), acidosis, hypertension, postoperative complications (such as recurrence of the TEF, esophageal stricture formation, and gastro‐esophageal reflux) may negatively affect the short‐ and long‐term clinical outcomes . It is also not known what surgical technique is associated with the best outcome …”
Section: Introductionmentioning
confidence: 99%
“…Comorbidities, intraoperative events like duration of surgery, the occurrence of hypercapnia (and its effect on cerebral autoregulation), acidosis, hypertension, postoperative complications (such as recurrence of the TEF, esophageal stricture formation, and gastro-esophageal reflux) may negatively affect the short-and long-term clinical outcomes. [11][12][13][14][15] It is also not known what surgical technique is associated with the best outcome. 12,16 In this paper we describe the perioperative courses of vital parameters and metabolic derangements as well as the short-term outcome in relation to the type of surgical approach in 101 consecutive neonates undergoing esophageal atresia type C repair.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation